Structural Identification of Nonlinear Coefficient Functions in Transport Processes through Porous Media - Knabner, Peter; Igler, B. A. (Lectures on Applied Mathematics, 2000)
Mathematical models provide the starting point for the simulation of complex processes, which arise in the natural and engineering sciences. Characteristic properties of the considered systems are represented by model parameters or coefficients. These have to be determined by experiments. If the coefficients are not measured directly, as direct measurements are not possible or do not lead to satisfying results, numerical identification procedures have to be applie